An Examination of Whether Mindfulness Can Predict the Relationship Between Objective and Subjective Attitudinal Ambivalence - Weng, Jennifer; DeMarree, Kenneth G. (Frontiers in Psychology, 2019)
Ambivalence is a mixed reaction toward an attitudinal object. Ambivalence is often viewed as aversive and people are motivated to reduce it. However, the presence of both strong positive and negative attitudes toward an object (objective ambivalence; OA) does not always lead to consciously experienced conflicted and torn feelings (subjective ambivalence; SA) or psychological discomfort. We hypothesized that the way people think about their inner experience can affect whether ambivalent attitudes lead to increased conflicted feelings. In five studies, we examined whether mindfulness predicts the relationship between objective and subjective ambivalence. We predicted that the acceptance aspect of mindfulness would attenuate the relationship between OA and SA, based on the idea that acceptance makes people more tolerant and less judgmental toward their inner states in general (and OA in particular). Although some findings across five studies were consistent with the prediction showing that acceptance attenuated the OA–SA relationship, other findings were not and even showed that acceptance strengthened the OA–SA relationship. A meta-analysis of the interaction effect across all studies failed to find support for predictions (r = -0.036 and 95% CI [-0.087; 0.022]). We discuss possible reasons for these mixed findings, and the implications of these studies.